Non-tuberculous mycobacteria and other acid fast bacilli pathogens identification by qPCR and MALDI-ToF MS in tuberculosis-like lesions of slaughtered cattle from Ecuador - Orlando, Solon Alberto; Vera Loor, Leila Estefania; Calderón, Joselyn; Carvajal-Capa, Melissa Joseth; Arcos Alcívar, Fabrizio; Torres-Lasso, Pablo; Maza Valle, W. Favián; Vargas González, Oliverio N.; Mora-Jaramillo, Naomi; León-Sosa, Ariana; Rivera, Ariana; Rodríguez-Pazmiño, Angel Sebastián; et al. (Frontiers in Veterinary Science, 2025)
IntroductionMycobacterial infections are caused by the Mycobacterium tuberculosis complex (MTBC) but also by non-tuberculous mycobacteria (NTM). While the importance of NTM in opportunistic infections in humans has been gaining attention, surveillance and control programs for cattle health and production remain predominantly focused on bovine tuberculosis (BTB) that it is caused exclusively by MTBC.MethodsIn this study, we conducted a comprehensive inspection of 5,803 cattle carcasses destined for human consumption across 22 abattoirs in five provinces of Ecuador’s coastal region, searching for lesions visually compatible with BTB (BTB-like lesions).ResultsA high prevalence of 13.4% (CI 95%: 12.8–14.6) for BTB-like lesions and 3.1% (CI 95%: 2.6–3.5) for acid-fast bacilli (AFB) presence in lesions was observed. From these lesions, we isolated 48 AFB cultures, 44 of which tested positive for NTM. Strikingly, MTBC was not found in any BTB-like lesion by qPCR. Furthermore, Matrix Assisted Laser Desorption/Ionization Time of Flight Mass Spectrometry (MALDI-ToF MS) identified six NTM species: M. neoaureum, M. fortuitum, M. novocastrense, M. asiaticum, M. duvalii, and M. mucogenicum. Additionally, other AFB opportunistic pathogenic species were identified, including Tsukamurella paurometabola, Gordonia hongkongensis, and Nocardia spp.DiscussionConsidering the potential misdiagnosis of NTM and other AFB species, BTB surveillance and control programs for MTBC should be revised to consider other opportunistic infections with similar clinical output to BTB.